Expression and bioinformatics analysis of RPL38 protein and mRNA in gastric cancer: RPL38 protein and mRNA in gastric cancer analysis - Qin, Yin; Liu, Lianfang; Hu, Xia; Zhang, Yonghua; Pan, Yingying; Gao, Haijian (Cellular and Molecular Biology, 2023)
We aimed to clarify the expression of RPL38 in gastric cancer, explore the relationship between the expression level of RPL38 and the clinicopathological parameters and prognosis of gastric cancer patients, and explore whether RPL38 has the potential to be used as a therapeutic target for gastric cancer and a biomarker for assessing prognosis. The mRNA and protein expression of RPL38 in gastric cancer tissues and normal tissues were compared by TIMER, Kaplan-Meier plotter, CCLE and UALCAN databases, respectively. Next, the relationship between the expression level of RPL38 in gastric cancer tissues and clinicopathological features was analysed using the UALCAN database. The Kaplan-Meier plotter database was then used to predict the prognostic value of RPL38 in gastric cancer patients, and overall survival curves were plotted based on the follow-up information of clinical specimens. The relationship between RPL38 expression and the level of immune infiltration in gastric cancer was explored using the TIMER database. Finally, co-expression analysis as well as enrichment analysis of RPL38 was performed using LinkedOmics database and GSEA, respectively. Through comprehensive bioinformatics analysis and immunohistochemistry experiments, we comprehensively concluded that RPL38 was highly expressed in gastric cancer. Univariate analysis showed that TNM stage (P=0.008), radiotherapy (P=0.02), and RPL38 expression level (P=0.0006) were associated with prognosis. Multifactorial analysis showed that RPL38 expression level (P=0.019), TNM stage (P=0.015) and radiotherapy (P=0.039) were independent risk factors affecting the prognosis of gastric cancer. Gastric cancer patients with high expression of RPL38 had poorer OS. In addition, RPL38 was associated with immune infiltration in gastric cancer. RPL38 is highly expressed in gastric cancer tissues, and RPL38 protein plays an important role in the development of gastric cancer, which is one of the important factors in assessing the prognosis of gastric cancer patients.